Transversal Skills in Vocational Education and Training: The Case of ENSAM Engineering Students - El Ajraoui, Toufik; Kaddour, Khalid Ben; Zeriouh, Mohammed (European Scientific Journal, ESJ, 2019)
This study deals with 4th year ENSAM (École Nationale Supérieure d’Arts et Métiers, Meknes, Morocco) engineering students who are studying English for engineering through Project-Based Learning (PBL). It attempts to describe how PBL helps develop students’ transversal skills, namely critical thinking skills, interpersonal skills, and media and information literacy skills. The importance of such skills is reflected in the success of the learning process as well as the academic achievement of the targeted students. In addition, these skills get more importance when engineering students seek effective employability and successful integration in the job market. A field study has been carried out among 240 students who have responded to a close-ended questionnaire for a quantitative research in addition to a qualitative analysis of such numerical results. The analyzed findings reveal an overall positive response to the integration of PBL in the English class, stressing that this form of contextualized learning has helped the respondents develop the three sets of transversal skills above. General conclusions are presented and highlighted for other similar investigations.